'A More Receptive Crowd than Before': Explaining the World Bank's Gender Turn in the 2000s. (July 2018) - Jones, Ben
In the mid-2000s, the gender work of the World Bank took a different turn with a new Gender Action Plan. Up until then, gender equality had been on the margins of the World Bank, concentrated around a small number of advocates. This particular articulation of gender took as its tagline 'gender equality as smart economics'. The Plan attracted three times the original budget of US24.5 million, and moved gender analysis into new fields of work: labour, work, land and agriculture rather than the more usual areas of health and education. It emerged at a time when gender work was becoming more legitimate in the field of development economics; where World Bank economists were 'a more receptive crowd than before'. The mid-2000s was also a time when the World Bank was becoming more conscious of its use of media technologies. The article draws on these two elements—economics and the use of media—to suggest the broader environment against which gender agendas take on meaning. Structural shifts in the field of development economics—the dominant discipline at the World Bank—made work on gender more legitimate and credible, and made World Bank staff 'a more receptive crowd than before', while the increasing use of media technologies meant the World Bank was conscious of how its work looked to outside audiences. These elements, only loosely related to what we might think of 'gender' as a normative agenda, nonetheless, changed what gender meant to many people working within the World Bank.